Mengenalkan Literasi Siswa Kelas Awal Disaat Pandemi Melalui Pembelajaran Daring Dengan Media Buku Besar untuk Meningkatkan Minat Membaca Siswa - Hardiyanti Hardiyanti (Universitas Sebelas Maret, 2020)
Reading is an activity or cognitive process that seeks to find various information contained in writing. This means reading is a thinking process to understand the contents of the text read. Through reading activities a person can find out what was previously unknown. Reading skills possessed by students have a great influence in determining success in following the learning process. Students who are able to read well and quickly will achieve good learning outcomes as well. Through the Big Book media, it is hoped that students will be able to improve their literacy by reading through interesting pictures according to the characteristics of students in the early grades, who are more interested in seeing pictures than those in the first grade. only in the form of writing. With the Bigbook media, students' curiosity will appear and they will start reading through the pictures they see. Of course, it will be different because it introduces literacy online because it is still during the covid-19 pandemic which has not allowed students to meet face-to-face at school. This is a dilemma for teachers to introduce literacy to their students through online learning.